Internalizing the Spirit of Mutual Cooperation in Housing Communities Implementation of Social Values - Sigit Triyono; M. Ridha Ilhami; Fatwa Nur'aini; Raihanah Sari; Sovia Husni Rahmia (The Kalimantan Social Studies Journal, 2025)
This study aims to examine the role of mutual cooperation activities in maintaining social solidarity in Semangat Village, a village with a fairly dense population. Although large populations are often a challenge in building harmonious social relationships, the results of the study show that the values of mutual cooperation are still very well maintained and closely intertwined. Gotong Royong activities in this village not only function in the physical aspect, but also in strengthening social relations between residents, building a sense of togetherness, and caring for each other. However, the main challenge faced is the low participation of the younger generation, which is affected by the changes in modern lifestyles. Therefore, efforts are needed to adapt gotong royong activities to the times, including the use of technology and social media. This study concludes that, with the right strategy, gotong royong activities in Semangat Village can continue to develop and provide greater social benefits, while maintaining the human values that are the basis of the life of the village community.